2018
DOI: 10.5812/asjsm.13025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Intensity Resistance Training on Circulating Levels of Irisin in Healthy Adults: A Randomized Controlled Trial

Abstract: Background: Existing research suggests that irisin increases in response to exercise in humans. However, results are controversial and a majority of the studies lack a control group. The present study aimed to analyze the effects of both one-bout, and three-week intense resistance training on physical fitness (body composition and strength) and serum irisin levels when compared to a control group. Methods: A total of 26 healthy young adults (n = 14 males; 12 females) completed the pre-assessment phase, and wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…In a study by Hecksteden et al (2013) , the group performing aerobic and resistance exercises for 26 weeks showed no significant changes in the irisin level as compared to the control group. In a study conducted on healthy adults of the same age group as in this study, the irisin levels did not show any significant changes after short-term or 3-week long high-intensity resistance training exercises ( Fernandez-del-Valle et al, 2018 ). A review of the irisin level after a short-term exercise reported that the level increased by approximately 15% on an average ( Fox et al, 2018 ), but a review of the irisin level after a long-term exercise reported no change after the exercise ( Qiu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 49%
“…In a study by Hecksteden et al (2013) , the group performing aerobic and resistance exercises for 26 weeks showed no significant changes in the irisin level as compared to the control group. In a study conducted on healthy adults of the same age group as in this study, the irisin levels did not show any significant changes after short-term or 3-week long high-intensity resistance training exercises ( Fernandez-del-Valle et al, 2018 ). A review of the irisin level after a short-term exercise reported that the level increased by approximately 15% on an average ( Fox et al, 2018 ), but a review of the irisin level after a long-term exercise reported no change after the exercise ( Qiu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 49%
“…Several kinds of physical exercise increased irisin blood levels among healthy people as well. High-intensity interval training increased irisin in young, healthy males [41,60] and healthy young adults [43], military aerobic training [48] increased irisin blood levels in young, healthy males and one study with a single group design found a significant increase in irisin in young females after treadmill exercise [37]. On the other hand, cycle ergometer-sprint training, consecutive training [77] as well as indoor running [64] led to a decrease of irisin blood levels in young, healthy males, and the same effect was found after basketball training in healthy children [39] or after taekwondo training in obese children [70].…”
Section: Summary Of Main Results and Interpretationsmentioning
confidence: 90%
“…The basic description of the included studies is presented in Table 2. [38] Iran RCT Obese with metabolic syndrome 54 F 53.5 (6.5) Dündar [39] Turkey RCT Healthy 34 M 14.5 (1.1) Dünnwald [40] Austria NRT; N-CG Type II diabetes 14 T 59.6 (5.7) * Eaton [41] Canada SGS Healthy 9 M 20.5 (1.5) Ellefsen [42] Germany SGS Healthy 18 F 26.0 (6.0) Fernandez-del-Valle [43] US RCT Healthy 26 T 21.2 (1.9) * Ghanbari-Niaki [44] Iran RCT Healthy 24 F 55.7 (4.9) Hecksteden [45] Germany RCT Healthy 102 T 49.0 (7.0) * Huang [46] China SGS Obese 22 T 22.1 (2.8)…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Öte yandan, kronik egzersize yanıt olarak irisin ve FNDC5 düzeylerinin azaldığı gösterilmiştir [2,13,20,21]. Egzersizin irisin ve FNDC5 seviyelerini etkilemediğini bildiren çalışmalar da vardır [7,13,22,23]. Veriler arasındaki uyumsuzluklar, deneklerin yaşı, cinsiyeti, sedanter veya sporcu olmaları, yapılan egzersizlerin akut veya kronik olması, uygulanan egzersizin tipi, şiddetti ve süresi arasındaki farklılıklardan kaynaklanıyor olabilir.…”
Section: Introductionunclassified